Semiotic Analysis of Traditional Food from Simalungun - Angel Tamaro Sijabat; Harahap, Ahmad Bengar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the meanings and symbols of Simalungun Traditional Food. The research method used in this study is a qualitative method with Charles Sanders Peirce's semiotic analysis, where signs are divided into 3 aspects of representation, object, and interpretation. Data collection was carried out through literature studies and in-depth interviews with resource persons from the Simalungun community, more precisely in Upper Simalungun. Based on the results of the research, interviews and literature were analyzed in a structured manner. The results of the study show that Simalungun traditional food contains many deep meanings such as hopes and advice to its recipients, especially traditional food, traditional food in Simalungun plays a very important role in Simalungun traditional events. Although not all of the traditional food is used as traditional food, the traditional food also has a very deep meaning that is more attached to the history of the struggle for survival of the ancestors of Simalungun. Every meaning implied in the food is very positive and good. This can help to increase understanding and appreciation of local cultural heritage, which in turn can support the development of inclusive and sustainable multicultural education.